Baseline mutational profiles of patients with carcinoma of unknown primary origin enrolled in the CUPISCO study☆ - Westphalen, Christoph Benedikt; Federer-Gsponer, Joël; Pauli, C.; Karapetyan, A. R.; Chalabi, N.; Durán-Pacheco, G.; Beringer, A.; Bochtler, Tilmann; Cook, N.; Höglander, E.; Jin, D. X.; Losa, F.; et al. (ESMO open, 2023)
Background - Patients with unfavorable carcinoma of unknown primary origin (CUP) have an extremely poor prognosis of ∼1 year or less, stressing the need for more tailored treatments, which are currently being tested in clinical trials. CUPISCO (NCT03498521) was a phase II randomized study of targeted therapy/cancer immunotherapy versus platinum-based chemotherapy in patients with previously untreated, unfavorable CUP, defined as per the European Society for Medical Oncology guidelines. We present a preliminary, descriptive molecular analysis of 464 patients with stringently diagnosed, unfavorable CUP enrolled in the CUPISCO study. - Materials and methods - Genomic profiling was carried out on formalin-fixed, paraffin-embedded tissue to detect genomic alterations and assess tumor mutational burden and microsatellite instability. - Results - Overall, ∼32% of patients carried a potentially targetable genomic alteration, including PIK3CA, FGFR2, ERBB2, BRAFV600E, EGFR, MET, NTRK1, ROS1, and ALK. Using hierarchical clustering of co-mutational profiles, 10 clusters were identified with specific genomic alteration co-occurrences, with some mirroring defined tumor entities. - Conclusions - Results reveal the molecular heterogeneity of patients with unfavorable CUP and suggest that genomic profiling may be used as part of informed decision-making to identify the potential primary tumor and targeted treatment options. Whether stringently diagnosed patients with unfavorable CUP benefit from targeted therapies in a similar manner to those with matched known primaries will be a key learning from CUPISCO.